Metachromatic leukodystrophy: magnetic resonance imaging (diffusion weighted image--DWI) - Seidl, Zdenek; Vaneckova, Manuela; Vitak, Tomas (Neuro endocrinology letters, 2008)
Ten years old patient with juvenile form of metachromatic leukodystrophy (MDL) is presented. Apart from standard magnetic resonance (MR) protocol, the diffusion weighted sequence was performed and apparent diffusion coefficient (ADC) map was constructed. The cause of restricted diffusion is considered to be the deposits of metachromatic substance in the intercellular space, apparently similar reason for decrease of speed of diffusion in other storage diseases.
Keywords: difuzní magnetická rezonance; lidé; Child; dítě; Leukodystrophy, Metachromatic; metachromatická leukodystrofie; Humans; Diffusion Magnetic Resonance Imaging